The frequency of lipoid nephrosis in the services of the first chair of the medical clinic, medical and therapeutic nosography Hospital "Dos de Mayo" - Zegarra Puppi, José (1957)
As seen, is under review the concept of nephrosis lipoid as primary renal tubular disease and exclusive; Today it is considered that the renal tubules to undergo aggression it will share in the glomerulus; would thus missing the concept of lipoic nephrosis and emerge the new glomerular nephrosis.